Berawan of Loagan Bunut: death and its sacred forbiddance - Selamat, Abu Zarrin; Mohd Salim, Sara Shakilla; Naning, Fatin Hana; Muhaidin, Munirah; Lee Feng, Koo; Magiman, Mohamad Maulana (Human Resources Management Academic Research Society (HRMARS), 2024)
There are sacred forbiddance or taboos in every culture, and funeral rites are no exception. Various societies possess customary practises and formal observances to cope with the concept of mortality. Familiarity with sacred forbiddance is crucial as it serves as guidelines and regulations in the administration of funeral rites. This study delves into the sacred forbiddances that are observed during the funeral proceedings, specifically those that occur prior to and subsequent to the burial for Berawan ethnic in Loagan Bunut, Sarawak, Malaysia. The discussions will be framed by the Bridging Reference Approach. This approach proves to be beneficial in maintaining the coherence and comprehensibility of a text or conversation by establishing connections between ideas and facilitating the understanding of the relationships between different pieces of information. The Berawan ethnic group follows a number of forbiddances. The prohibition varies depending on who dies and how they die. However, many of the practices have changed as a result of the passage of time and the influence of religions such as Islam and Christianity. It was also discovered that the current generation has no idea why such a prohibition was imposed; they simply adhere to certain rules and restrictions.